2012
DOI: 10.1111/nmo.12002
|View full text |Cite
|
Sign up to set email alerts
|

The neural crest‐ and placodes‐derived afferent innervation of the mouse esophagus

Abstract: The TRPV1-positive (potentially nociceptive) vagal afferent neurons innervating the mouse esophagus originate from both neural crest and placodes. The expression profile of the receptors for neurotrophic factors is similar between the neural crest-derived vagal and spinal nociceptors, but distinct from the vagal placodes-derived nociceptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 54 publications
8
38
0
Order By: Relevance
“…No product was amplified from negative (bath) controls ( n = 39) indicating negligible probability of false positive results. In our previous studies we have also reported negligible false positive rates (<1%, n = 640 negative controls) …”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…No product was amplified from negative (bath) controls ( n = 39) indicating negligible probability of false positive results. In our previous studies we have also reported negligible false positive rates (<1%, n = 640 negative controls) …”
Section: Methodsmentioning
confidence: 59%
“…Spinal T2 and T3 DRG ganglia were harvested 10–15 days after the injections. Single cell RT‐PCR was performed on individual neurons as described previously . The sensory ganglia were dissected, enzymatically dissociated, and the neurons were plated on poly‐ d ‐lysine/laminin‐coated coverslips.…”
Section: Methodsmentioning
confidence: 99%
“…As germline Cdh1 knockout led to embryonic lethality [8], we crossed Wnt1-Cre mice [22] Figure S2A). We harvested RNAs from different tissues and found reduced Cdh1 mRNA levels in dorsal root ganglion of Cdh1 Wnt1 mice (Supplementary information, Figure S2B) [23]. Intriguingly, we found that Cdh1…”
Section: Cdh1 Conditional Knockout Mice Displayed Various Craniofaciamentioning
confidence: 75%
“…Its main function is to transport the food into the stomach by a propulsive contraction wave. Peristaltic movement of the esophagus is controlled by nerves of vagal motor neurons and the ganglionated myenteric plexus . The myenteric plexus of the esophagus (a part of the enteric nerve system) is derived from the neural crest, while the vagal neurons are derived from both the neural crest and cranial placodes .…”
Section: Introductionmentioning
confidence: 99%
“…Peristaltic movement of the esophagus is controlled by nerves of vagal motor neurons and the ganglionated myenteric plexus . The myenteric plexus of the esophagus (a part of the enteric nerve system) is derived from the neural crest, while the vagal neurons are derived from both the neural crest and cranial placodes . Esophageal innervation is first observed in the rostro‐most regions of the esophagus at E13, and develops in a rostrocaudal progression that is coincident with esophageal muscle differentiation .…”
Section: Introductionmentioning
confidence: 99%